Leguminosae, Dipterocarp Aceae, Burseraceae - Important Sources of Biodynamic Compound Resins - Khan, G. L. (Indian Forester, 2004)
Although many Indian gums and resins have been in commerce from several hundred years emergence of certain synthetic substitute from the last few decades have been responsible to some extent for the decline of the importance of the natural products. However, many of the synthetic substance have been found to be toxic to human beings and this has reversed the trend to natural product usage. Now for this millennium if the trend of greater emphasis on utilization of natural plant products continue in the western countries, then the best source of these products would be the tropical countries like India should playa vital role in this regard. Tribes and tribal areas are the main source of these resinous exudates. There exist a large confusion in literature while describing resins. Several resinous material have been described as true gums. These resins and gums are used in large amounts as binding, thickening, emulsifying, stabilizing, sizing, water-proofing agents, as coagulants, as settling or filter aids in almost all the industries as Pharmaceuticals, food, paper, textiles, cosmetics, food, paints, inks. In this paper and previous two papers we have tried to put the scientific data in proper manner for future studies. In the present context of intellectual property right it is of paramount importance that all the resins being produced in India, should be properly documented with their chemistry, botany, and utilization. This would greatly check the hijacking of these products for patenting by other countries.